1983
DOI: 10.1161/01.hyp.5.4_pt_2.ii109
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypertension in hemodialysis patients with nifedipine.

Abstract: The hemodynamic effects of nifedipine were studied in nine patients with acute or chronic renal failure undergoing hemodialysis. Arterial blood pressure was lowered within 15 minutes of oral administration of nifedipine 10 mg. Mean arterial pressure and total systemic peripheral resistance were significantly decreased, whereas cardiac index and heart rate revealed slight but statistically insignificant changes. Changes in pulmonary artery diastolic pressure and mean right atrial pressure which were closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nifedipine is a calcium blocking agent with vasodilating properties (Robinson et al, 1980); this drug is being increasingly used in the treatment of angina pectoris and hypertension in uraemic patients, predisposed to cardiovascular disease (Kubo et al, 1983;Lewin & Trautman, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Nifedipine is a calcium blocking agent with vasodilating properties (Robinson et al, 1980); this drug is being increasingly used in the treatment of angina pectoris and hypertension in uraemic patients, predisposed to cardiovascular disease (Kubo et al, 1983;Lewin & Trautman, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The antihypertensive efficacy of the calcium antagonist nifedipine has been well established not only in essential hypertension (Aoki et al 1978;Krebs et al 1982), but also in patients with hypertension secondary to chronic renal failure (Kleinbloesem et al 1985;Kubo et al 1983;Kusano et al 1982Kusano et al , 1984. We have recently found that due to decreased protein binding, its pharmacokinetics are altered in patients with chronic renal failure, resulting in larger volumes of distribution and longer half-lives (Kleinbloesem et al 1985).…”
mentioning
confidence: 99%